Geodetic mass balance of Abramov Glacier from 1975 to 2015 - Florian Denzinger; Horst Machguth; Martina Barandun; Etienne Berthier; Luc Girod; Marlene Kronenberg; Ryskul Usubaliev; Martin Hoelzle (Journal of Glaciology, 2021)
Multi-decadal mass loss estimates are available for few glaciers of Central Asia. On Abramov Glacier (Pamir-Alay, Kyrgyzstan), comprehensive long-term glaciological measurements have been carried out from 1968 to 1999 and re-initiated in 2011. A climatological interpretation of this benchmark glacier in Central Asia requires bridging the gap between historical and renewed measurements. This is achieved here by computing the geodetic mass balance from 1975 to 2015 using previously unreleased Soviet aerial imagery and Pléaides stereo-imagery. During 1975–2015, Abramov Glacier lost 2.2 km2 (8.2%) of its area. The mean annual thickness change was − 0.43 ± 0.14 m a−1 for the period 1975–2015, corresponding to a volume change of − 0.45 ± 0.15 km3. The average specific geodetic mass balance amounts to − 0.38 ± 0.12 m w.e. a−1. The 1975–2015 glacier mass loss lies within the range of glaciological and geodetic mass-balance estimates that were previously published for disparate and shorter time intervals since 1968. This study covers a much longer time period than earlier geodetic estimates and demonstrates the capacity to geodetically constrain glacier change at high spatial resolution in Central Asia using historic aerial imagery and Structure from Motion techniques. Therefore, it could serve as a benchmark for future studies of regional mass change.